Optimized Protocols for In-Vitro T-Cell-Dependent and T-Cell-Independent Activation for B-Cell Differentiation Studies Using Limited Cells - Marsman, Casper; Verhoeven, Dorit; Koers, Jana; Rispens, Theo; ten Brinke, Anja; van Ham, S. Marieke; Kuijpers, Taco W. (Frontiers in Immunology, 2022)
For mechanistic studies, in vitro human B cell differentiation and generation of plasma cells are invaluable techniques. However, the heterogeneity of both T cell-dependent (TD) and T cell-independent (TI) stimuli and the disparity of culture conditions used in existing protocols makes interpretation of results challenging. The aim of the present study was to achieve the most optimal B cell differentiation conditions using isolated CD19+ B cells and PBMC cultures. We addressed multiple seeding densities, different durations of culturing and various combinations of TD stimuli and TI stimuli including B cell receptor (BCR) triggering. B cell expansion, proliferation and differentiation was analyzed after 6 and 9 days by measuring B cell proliferation and expansion, plasmablast and plasma cell formation and immunoglobulin (Ig) secretion. In addition, these conditions were extrapolated using cryopreserved cells and differentiation potential was compared. This study demonstrates improved differentiation efficiency after 9 days of culturing for both B cell and PBMC cultures using CD40L and IL-21 as TD stimuli and 6 days for CpG and IL-2 as TI stimuli. We arrived at optimized protocols requiring 2500 and 25.000 B cells per culture well for TD and TI assays, respectively. The results of the PBMC cultures were highly comparable to the B cell cultures, which allows dismissal of additional B cell isolation steps prior to culturing. In these optimized TD conditions, the addition of anti-BCR showed little effect on phenotypic B cell differentiation, however it interferes with Ig secretion measurements. Addition of IL-4 to the TD stimuli showed significantly lower Ig secretion. The addition of BAFF to optimized TI conditions showed enhanced B cell differentiation and Ig secretion in B cell but not in PBMC cultures. With this approach, efficient B cell differentiation and Ig secretion was accomplished when starting from fresh or cryopreserved samples. Our methodology demonstrates optimized TD and TI stimulation protocols for more in-depth analysis of B cell differentiation in primary human B cell/PBMC cultures while requiring low amounts of B cells, making them ideally suited for future clinical and research studies on B cell differentiation of patient samples from different cohorts of B cell-mediated diseases.